CONVERSATIONAL IMPLICATURE IN DIALOGUE OF “LAYAR TERKEMBANG” NOVEL BY SUTAN TAKDIR ALISJAHBANA - TIKA MULIYANI; MEISURI MEISURI; WIDYA ANDAYANI (State University of Medan, 2020)
This research dealt with Conversational Implicature in Dialogue of LayarTerkembang Novel By SutanTakdirAlisjahbana based on Grice’s Theory and it was aimed to finding out the types of conversational implicature, and to describe why the certain type of conversational implicature becomes dominant. This research was conducted by using descriptive qualitative method. The source of the data was taken from LayarTerkembang novelby SutanTakdirAlisjahbana, Then the dialogue of the novel as the data for the research. The findings showed that there were two types of conversational implicature in the procedures namely Generalized Conversational Implicature belong to 33 utterances and Particularized Conversational Implicature belong to 36 utterances. So, the most dominant types of conversational implicaturebetween the main characters in the novel was particularized conversational implicature because it more contained ambiguity, implicit meaning, conveyed an additional meaning, and their response did not relevant with every question and also it cannot easily to understand what he/she was talking about.